Perancangan dan Pembuatan Aplikasi Pembelajaran Vocabulary dan Grammar untuk Anak SMP Berbasis Web - Abel, Bill Roger; Rostianingsih, Silvia; Gunadi, Kartika (Jurnal Infra, 2016)
Vocabulary and grammar learning at junior highschool are the most important fundamental to improve studentâs ability to understand English. Mastering vocabulary and grammar can make the students better and more fluent in speaking English. With the use of learning media, vocabulary and grammar learning for students will be more interesting and studentâs results of learning will be increased.This learning website features various type of practices like drag and drop, swap words in sentence, match words and pictures and sound. Using the 2006 curriculum based course and with the source of 7th grade Junior Highschool teacher, this learning website is adjusted to the needs of 7th grade Junior Highschool students. Making of this website is using the PHP, HTML5 language and using the Facebook API to make the students easier to share their test results.Berdasarkan kuesioner yang di bagikan, desain tampilan serta bentuk latihan soal aplikasi ini dinilai sangat menarik, tetapi materi yang diberikan belum dipahami secara baik oleh siswa.The results obtained from the application that has been made are the design and features of this application can run well on several browser. Grammar and vocabulary practices feature on this application are easy to access and understand by the user. Based on questionnaires, the design and practices of this application is considered very interesting, but the provided courses has not been well understood by the students.